1998
DOI: 10.1001/archpedi.152.6.540
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Infant Death With External Airways Covered

Abstract: To study factors associated with sudden infant deaths occurring with the external airways (ie, nose and mouth) covered by bedding. Design: Case-comparison study of infants dying with vs those dying without the external airways covered. Setting: Death-scene investigation and reconstruction at the site of death using an infant mannequin; 18 metropolitan areas. Participants: Caregivers for a consecutive sample of infants who died of sudden infant death syndrome (SIDS). Complete data from 206 of 382 eligible cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Other studies have demonstrated that African-American mothers have higher rates of bedsharing than Caucasian families,(6, 9, 10) and the SIDS risk during bedsharing is greater when combined with other risk factors such as smoking, consumption of alcohol, medications, or drugs that alter arousal, young (<3 months) infant age, use of bedding and soft surfaces, bedsharing with persons other than the parents, and extended bedsharing (i.e., all night long). (2, 3538) Bedsharing among African-American women is viewed as a very efficient way to provide physiological comfort to the mother and child, while being able to monitor the infant's breathing and general health. (15) In addition, some African-American women bedshared with their infant because there was no other space for the infant.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated that African-American mothers have higher rates of bedsharing than Caucasian families,(6, 9, 10) and the SIDS risk during bedsharing is greater when combined with other risk factors such as smoking, consumption of alcohol, medications, or drugs that alter arousal, young (<3 months) infant age, use of bedding and soft surfaces, bedsharing with persons other than the parents, and extended bedsharing (i.e., all night long). (2, 3538) Bedsharing among African-American women is viewed as a very efficient way to provide physiological comfort to the mother and child, while being able to monitor the infant's breathing and general health. (15) In addition, some African-American women bedshared with their infant because there was no other space for the infant.…”
Section: Discussionmentioning
confidence: 99%
“…There is a great deal of controversy among health professionals on this topic, as bedsharing and breastfeeding duration have been correlated, 19 but bedsharing also increases the risk of SIDS, suffocation, asphyxia, entrapment, and other sudden unexpected infant deaths. 2026 For such controversial topics, it is not surprising to find a high percentage of inaccurate websites (e.g., promotion of bedsharing as a strategy to encourage breastfeeding), as accuracy was determined solely by consistency with AAP recommendations. 10, 11 …”
Section: Discussionmentioning
confidence: 99%
“…5 However, many SIDS cases are not explained by the prone sleep position; indeed, 1 study from California failed to show any effect of prone position. 6 Other contributing factors have been suggested by some studies, including singly or in combination, parental smoking, 7-12 parental drug or alcohol abuse, 11,13,14 unsafe bedding, [15][16][17] and infanticide. 18,19 A recent assertion that some SIDS may be caused by congenital cardiac electrical instability (the long-QT syndrome) 20 has been severely challenged.…”
mentioning
confidence: 99%